Application of fluorescence in situ hybridisation using peptide nucleic acid probes in gastric samples for detection of Helicobacter pylori clarithromycin resistance - Cerqueira, L. (2011)
Microorganisms are responsible for several infectious diseases that can cause severe problems to patients and their treatment success is seriously correlated with the fast detection of the infectious agent. Some of the standard methods used, such as culturing methods are fastidious and time-consuming and do not give any information about the antibiotic resistance profile. Therefore, molecular methods have been developed during the last several years in order to overcome these shortcomings. In this work a new genotypic method that permits the identification of the microorganism in clinical samples in a prompt way is proposed. This technique is based on Fluorescence in situ hybridization with PNA probes that are synthetic molecules, complementary to a specific rRNA sequence of the microorganism. Methods: A set of PNA probes were designed concerning H. pylori point mutations regarding clarithromycin resistance which is the main problem of gastric diseases treatment failure. An additional probe concerning susceptibility was also designed. After hybridization conditions optimization, probes were applied to H. pylori smears to achieve their practical sensitivity and specificity. At the end they were applied to gastric biopsies in a retrospective study for method validation in real samples. E-test and PCR-sequencing were used to evaluate the results. Results: The probes concerning clarithromycin resistance hybridized only with the resistant strains that had the corresponding point mutations and as such presented 100% sensitivity (95% CI, 79.9-100) and 100% specificity (95% CI, 71.6-100). Results also showed that it is possible to discriminate susceptible from resistant H. pylori strains in gastric biopsy samples since it was presented similar results between the 3 tests used. Overall, the PNA-FISH method was in full agreement with PCR-sequencing although it was a little bit lower when compared to E-test that it was used as gold standard method in this retrospective study (86%). Conclusion: PNA-FISH proved to be an important in situ method for detection of microorganisms in clinical samples in a more prompt way than the standard methods. Due to high H. pylori probes sensitivity and specificity it is proved the applicability of PNA-FISH methodology to clinical material, thus overcoming the need of culturing steps and/or PCR/sequencing procedures and enabling rapid initiation of appropriate antibiotic therapy until culture confirmation several days later.